Pengembangan Media Video Animasi Berbasis Powtoon Pada Subtema 3 Usaha Pelestarian Lingkungan Sebagai Sumber Pembelajaran Di Sekolah Dasar - Fany Chaerun Nisa; R. Teti Rostikawati; Dendy Saeful Zen (Elementary Teacher Education Program, Majalengka University, 2023)
In the Batutulis 3 state elementary school, the media used is not yet varied and is digital based. Therefore, in this learning there is a need to develop learning media. The aim of this research is to produce animated video media products based on Powtoon. Theme 8, sub-theme 3 Environmental Conservation Efforts, learning 1 in class V at SDN Batutulis 3, Bogor City. This research uses Research and Development (R&D) by applying the Four D model (Define, Design, Development, Disseminate). Product testing was carried out by one media expert, one language expert, one material expert, 2 teacher responses and 20 student responses. The research results from media, language, material experts and teacher responses were declared very suitable for use, where the media expert's assessment was 100%, language expert's 84%, material expert's 94% and teacher response 1 was 98.6%, teacher response 2 was 98.6%. In the limited test phase, 20 students responded very well with an average percentage of 91.3% for the Powtoon-based animated video media used. Based on the research results, it can be concluded that Powtoon-based animated video media is declared very suitable for use as a learning medium.